Functionalization of cellulose fibers and paper with lanthanide-based luminescent core/shell nanoparticles providing 3-level protection for advanced anti-counterfeiting purposes. (June 2022) - Szczeszak, Agata; Skwierczyńska, Małgorzata; Przybylska, Dominika; Runowski, Marcin; Śmiechowicz, Emilia; Erdman, Aleksandra; Ivashchenko, Olena; Grzyb, Tomasz; Kulpiński, Piotr; Olejnik, Konrad
Graphical abstract: Highlights: Lanthanide-doped core@shell nanoparticles for luminescent cellulose fibers production. Dual-range excitation of luminescent materials with 975 and 1532 nm laser radiation. Luminescent fibers as anti-counterfeiting agents for documents, clothes and valuable products. '3-level' protection system resulting from a unique optical activity of the nanoparticles. Abstract: The increasingly wide-spreading falsification of documents, clothing, and packaging has a negative impact on every aspect of the global markets. Therefore, the development of high-quality strategies for materials protection has become a big challenge. Thus, this work presents novel anti-counterfeiting lyocell fibres, exhibiting bright green or yellowish up-conversion emission upon dual-range excitation, using either 975-nm or 1532-nm NIR laser radiation. The up-converting cellulose fibers were prepared by introducing lanthanide-doped core@shell nanoparticles β-NaYF4 : Yb 3+, Er 3+ @β-NaYF4 into the cellulose matrix. The spinning process of fibres was based on N-methylmorpholine N-oxide method, environmentally friendly because of the reusable reagents used. The prepared fibres were incorporated into the paper mass, forming a luminescent paper as a proof of concept for the multi-modal protection of documents. The luminescent fibres have considerable application potential as anti-counterfeiting composite materials with excellent performance, which are very difficult to imitate or copy, providing a very high level of security.